Chatting with the neighbors: crosstalk between Rho-kinase (ROCK) and other signaling pathways for treatment of neurological disorders - Hensel, Niko; Rademacher, Sebastian; Claus, Peter (Frontiers in Neuroscience, 2015)
ROCK inhibition has been largely applied as a strategy to treat neurodegenerative diseases (NDDs) and promising results have been obtained in the recent years. However, the underlying molecular and cellular mechanisms are not fully understood and different models have been proposed for neurodegenerative disorders. Here, we aim to review the current knowledge obtained for NDDs identifying common mechanisms as well as disease-specific models. In addition to the role of ROCK in different cell types such as neurons and microglia, we focus on the molecular signaling-pathways which mediate the beneficial effects of ROCK. Besides canonical ROCK signaling, modulation of neighboring pathways by non-canonical ROCK-crosstalks is a recurrent pattern in many NDD-model systems and has been suggested to mediate beneficial effects of ROCK-inhibition.